Reward Expectations Lead to Smoking Uptake among Depressed Adolescents - Audrain-McGovern, Janet (2011)
AIMS: While the comorbidity between adolescent depression and smoking has been well documented, less is known about why smoking is disproportionately higher among depressed adolescents. Emerging research suggests that reward-related mechanisms may be important to consider. This study sought to determine whether adolescents with higher depression symptoms have greater smoking reward expectations, which in turn, influence smoking progression. PARTICIPANTS: The sample was composed of 1,393 adolescents participating in a longitudinal survey study of adolescent health behaviors. DESIGN AND MEASUREMENTS: In this prospective cohort study, variables were measured via self-report every six months from age 14 to age 17 resulting in six waves of data. FINDINGS: Parallel processes latent growth curve modeling indicated that higher depression symptoms across mid to late adolescence predicted a 17% increase in smoking reward expectations (β = 3.50, z=2.85, p=.004), which in turn predicted a 23% increase in the odds of smoking progression (β= .206, z=3.29, p=.001). The indirect effect was significant with delta method (β(indirect) = .72, z= 3.09, p=.002; 95% CI= .26, 1.18) and bootstrap (β(indirect) = .72, z= 2.10, p=.03; 95% CI= .05, 1.39) standard errors. CONCLUSIONS: The study provides novel evidence that expectations of smoking reward facilitate smoking uptake among depressed adolescents. Smoking reward expectations may identify depressed adolescents at risk of smoking. Addressing alternative ways to meet the reward expectations rather than smoking may be an important component to consider in the preventing smoking and promoting smoking cessation among adolescents with elevated depression symptoms.